29.4: Influence of Measuring Environment on the Electrical Characteristics of a‐IGZO thin film transistors. (26th August 2021) - Liu, Nian; Feng, Zhengyu; Lu, Macai; Mei, Xueru; Liu, Minggang; Gao, Lu; Yao, Jiangbo
Abstract : In this paper, we disscuss the influence of measuring environment on the leakage current and Vth of ESL (Etching‐Stop‐Layer structure) and TG‐SA (Top‐Gate self‐aligned structure) a‐IGZO TFTs. Hydrogen and oxygen in air can accumulate on the surface of TFTs, forming electrode with floating potential. This layer coupled with input signal potential, results in Ioff increasing in both structure, and Vth shifting negatively in the ESL structure.